THE CHEMICAL QUALITY OF RICE BRAN DURING STORAGE USING CLOVE LEAF EXTRACT (SYZIGIUM AROMATICUM) - Lily Joris; Shirley Fredriksz; Arnold Ismael Kewilaa (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
The purpose of this research is to find out about the effect of Clove leaf (syzygium aromaticum) on the chemical quality of rice bran during storage. This research is done during a period of two months in the Food Technology and Engineering Laboratory of Pattimura, University’s Faculty of Agriculture. This research is an experiment using completely randomized design (CRD) with 4 treatments and 4 repetitions. The experiments are: K = 200gr rice bran without preservatives (control), K1 = 200gr rice bran with addition of 30ml clove leaf extract with 200gr water + 100gr clove leaves; with 1:1 ratio. K2 = 200gr rice bran with addition of 30ml clove leaf extract with 200gr water + 100gr clove leaves; with 1:2 ratio. K3 = 200gr rice bran with addition of 30ml clove leaf extract with 200gr water + 100gr clove leaves; with 2:1 ratio. The measure variables are: water content, ash content, fat, protein, and crude fiber. The results are analyzed using ANOVA in SPSS Version 19. If there are any differences in the results it would be further analyzed with the Duncan test. The results of this research shows that the use of clove extract in treatment with 2:1 ratio could maintain the chemical quality of rice bran (water content, ash content, fat, protein, and crude fiber.